Biotic interactions help explain variation in elevational range limits of birds among Bornean mountains - Ryan C. Burner; Andy J. Boyce; David Bernasconi; Alison R. Styring; Subir B. Shakya; Chandradewana Boer; Mustafa Abdul Rahman; Thomas E. Martin; Frederick H. Sheldon (Journal of Biogeography, 2020)
Aim Physiological tolerances and biotic interactions along habitat gradients are thought to influence species occurrence. Distributional differences caused by such forces are particularly noticeable on tropical mountains, where high species turnover along elevational gradients occurs over relatively short distances and elevational distributions of particular species can shift among mountains. Such shifts are interpreted as evidence of the importance of spatial variation in interspecific competition and habitat or climatic gradients. To assess the relative importance of competition and compression of habitat and climatic zones in setting range limits, we examined differences in elevational ranges of forest bird species among four Bornean mountains with distinct features. Location Bornean mountains Kinabalu, Mulu, Pueh and Topap Oso. Taxon Rain forest bird communities along elevational gradients. Methods We surveyed the elevational ranges of rain forest birds on four mountains in Borneo to test which environmental variables—habitat zone compression or presence of likely competitors—best predicted differences in elevational ranges of species among mountains. For this purpose, we used two complementary tests: a comparison of elevational range limits between pairs of mountains, and linear mixed models with naïve occupancy as the response variable. Results We found that lowland species occur higher in elevation on two small mountains compared to Mt. Mulu. This result is inconsistent with the expectation that distributions of habitats are elevationally compressed on small mountains, but is consistent with the hypothesis that a reduction in competition (likely diffuse) on short mountains, which largely lack montane specialist species, allows lowland species to occur higher in elevation. The relative influence of competition changes with elevation, and the correlation between lower range limits of montane species and the distribution of their competitors was weaker than in lowland species. Main conclusions These findings provide support for the importance of biotic interactions in setting elevational range limits of tropical bird species, although abiotic gradients explain the majority of distribution patterns. Thus, models predicting range shifts under climate change scenarios must include not only climatic variables, as is currently most common, but also information on potentially resulting changes in species interactions, especially for lowland species.

Occupancy patterns and upper range limits of lowland Bornean birds along an elevational gradient - Ryan C. Burner; Alison R. Styring; Mustafa A. Rahman; Frederick H. Sheldon (Journal of Biogeography, 2019)
Aim The traditional view of species’ distributions is that they are less abundant near the edges of their ranges and more abundant towards the centre. Testing this pattern is difficult because of the complexity of distributions across wide geographical areas. An alternative strategy, however, is to measure species’ distributional patterns along elevational gradients. We applied this strategy to examine whether lowland forest birds are indeed less common near their upper range limits on a Bornean mountain, and tested co‐occurrence patterns among species for potential causes of attenuation, including signatures of habitat selection and competition at the periphery of their ranges. Location Mt. Mulu, Borneo. Taxon Rain forest birds. Methods We surveyed lowland forest birds on Mt. Mulu (2,376 m), classified their elevation‐occupancy distributions using Huisman–Olff–Fresco (HOF) models, and examined co‐occurrence patterns of species pairs for signatures of shared habitat patches and interspecific competition. Results For 39 of 50 common species, occupancy was highest at sea level then gradually declined near their upper range edges, in keeping with a “rare periphery” hypothesis. With respect to habitat selection, lowland species do not appear to cluster together at sites of patchy similar habitat near their upper range limits; neither are most lowland species segregated from potential montane competitors where ranges overlap. Main conclusions High relative abundance at sea level implies that species inhabit “truncated niches” and are not currently near the limits of their fundamental niche, unless unknown critical response thresholds exist. However, indirect effects of increasing temperature predicted under climate change scenarios could still influence lower range limits of lowland species indirectly by altering habitat, precipitation regimes and competitive interactions. The lack of non‐random co‐occurrence patterns implies that patchy habitat and simple pairwise species interactions are unlikely to be responsible for upper range limits in most species; diffuse competition across diverse rain forest bird communities could still play a role.

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)